THE ROLE OF COLD STORAGE FACILITY IN AN EFFECTIVE INVENTORY MANAGEMENT SYSTEM -A CASE STUDY OF ASIAN FOOD SHOP IN FINLAND - Wang, Yiting (My University, 2017)
This thesis is a case study that want to find out an effective inventory management throughout a strategic cold storage facility. From case company’s shortage of cold storage problem, it will find out how can a cold storage facility effects the business growth and what the case company should do to solve current difficulties and achieve a satisfied result, which can also apply to the other small and medium sized enterprises with the same problem. It points out the difficulty of foreign SMEs doing small food business to have their own cold storage facility in Finland through the example of the case company, and it reminds inventory management of cold storage is also a big problematic situation for business growth that shall not be neglected.
Keywords: Cold storage; Inventory Management; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|